Keynesian vs Monetaris Approach: Which Model Effectively Controls Indonesia's Economy? - Ade Novalina (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
This study analyzes the phenomenon of the problem of different approaches in controlling the Indonesian economy. This study was able to predict using two different theories. Data analysis for long-term prediction uses Structural Factor-Augmented Vector Autoregression (SFAVAR). The result of the research shows that the model of controlling the rate of economic stability is done through inflation and export in short, medium and long-term. Policies are to control the poor in the short term through exports and inflation; in the medium term, foreign exchange reserves and exports; GDP and exports control long-term. Apparently, exports are very dominant in affecting economic stability.